Psychology from the Standpoint of the Subject - Boreham, Andrew. author. aut Link
VIII, 360 p.
Keywords: This book introduces the groundbreaking work of the German critical psychologist Klaus Holzkamp. In contrast to contemporary psychology's worldlessness, the writings present a concept of psychology based on the individual's relations to the world and open up new perspectives on human subjectivity, agency and the conduct of everyday life.